Pengaruh Debt Ratio (Dr), Working Capital To Total Assets (WCTA) Dan Current Ratio (CR) Terhadap Harga Saham Dengan Return On Assets (Roa) Sebagai Variabel Intervening Pada Perusahaan Property Dan Real Estate Di Bursa Efek Indonesia Periode 2017-2020 - Indah Nurcahyani; Budi Wahono; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to determine the effect of: 1. debt ratio (DR), working capital to total assets (WCTA) and current ratio (CR) to return on assets (ROA), (2) debt ratio (DR), working capital to total asset (WCTA), current ratio (CR) and return on assets (ROA) to the stock price, (3) debt ratio (DR), working capital to total assets (WCTA) and current ratio (CR) to the stock price by ROA as an intervening variable. The sampling technique used was purposive sampling and obtained data of 76 samples from 19 property and real estate company data. The data analysis technique using in research is path analysis . The result of this research showed that: DR has negative significant effect on ROA, WCTA has positive effect on ROA but not significant and CR has negative and not significant effect on ROA. DR has negative significant effect on stocks price, WCTA has negative an not significant effect on stocks price and CR has positive effect but not significant on stocks price. ROA has positive significant effect on stocks price. The result of sobel test showed that ROA is cannot mediate the effect of WCTA on stock prices. And able to mediate the effect of DR and CR on stock prices. Keywords: Debt Ratio, Working Capital To Total Assets, Current Ratio, Return On Assets, Stocks Price